Dampness and moulds in relation to respiratory and allergic symptoms in children: results from Phase Two of the International Study of Asthma and Allergies in Childhood (ISAAC Phase Two). Issue 7 (21st June 2013) - Weinmayr, G.; Gehring, U.; Genuneit, J.; Büchele, G.; Kleiner, A.; Siebers, R.; Wickens, K.; Crane, J.; Brunekreef, B.; Strachan, D. P.; ,
Summary Background Many studies report that damp housing conditions are associated with respiratory symptoms. Less is known about mechanisms and possible effect modifiers. Studies of dampness in relation to allergic sensitization and eczema are scarce. Objective We study the influence of damp housing conditions world‐wide on symptoms and objective outcomes. Methods Cross‐sectional studies of 8–12‐year‐old children in 20 countries used standardized methodology from Phase Two of the International Study of Asthma and Allergies in Childhood (ISAAC). Symptoms of asthma, rhinitis and eczema, plus residential exposure to dampness and moulds, were ascertained by parental questionnaires (n = 46 051). Skin examination, skin prick tests (n = 26 967) and hypertonic saline bronchial challenge (n = 5713) were performed. In subsamples stratified by wheeze (n = 1175), dust was sampled and analysed for house dust mite (HDM) allergens and endotoxin. Results Current exposure to dampness was more common for wheezy children (pooled odds ratio 1.58, 95% CI 1.40–1.79) and was associated with greater symptom severity among wheezers, irrespective of atopy. A significant (P < 0.01) adverse effect of dampness was also seen for cough and phlegm, rhinitis and reported eczema, but not for examined eczema, nor bronchial hyperresponsiveness. HDM sensitization was more common in damp homes (OR 1.16, 1.03–1.32). HDM‐allergen levels were higher in damp homes and were positively associated with HDM‐sensitization, but not wheeze. Conclusion A consistent association of dampness with respiratory and other symptoms was found in both affluent and non‐affluent countries, among both atopic and non‐atopic children. HDM exposure and sensitization may contribute, but the link seems to be related principally to non‐atopic mechanisms.